The usage of E-Wallet : A study among Universiti Utara Malaysia students - Aishah Siregar, Iskandar Zulkarnain (2023)
This study aims to examine The Usage of E-Wallets Among Students at Universiti Utara Malaysia (UUM). With the advancement of technology and the increasing popularity of e-commerce, e-wallets have emerged as a convenient and secure payment method. This research aims to explore the usage of e-wallets among UUM students, as well as their perceptions and experiences with this digital payment solution. The study employs a quantitative approach to capturing information on their demographic characteristics, ease of use, awareness of e-wallets, rewards, security, trust, and frequency of usage. Additionally, this method to gain deeper insights into their motivations, preferences, and concerns regarding e-wallet usage. The findings of this study will contribute to the existing literature on e-wallet usage, particularly among the UUM student population. The results will shed light on the factors that influence the acceptance and usage of e-wallets, providing valuable insights for e-wallet providers, policymakers, and other stakeholders in the digital payment ecosystem. Furthermore, the study will help identify potential scope for improvement and inform strategies to enhance the usage and usage of e-wallets among students at University Utara Malaysia.